Effect of the Magnetic Field and Rotation on Peristaltic Flow of A Carreau Fluid in Asymmetric Channel with Porous Medium - Rashid, Hamza; Hummady, Liqaa Z. (Iraqi Journal of Science, 2024)
In this paper, the instability of the Carreau fluid was discussed in the asymmetric channel with a porous medium in the presence of a changing magnetic field and rotation. The Carreau fluid behaves like a non-Newtonian fluid, where it was found that the rotation has an effect on the stability of the fluid. Numerical methods are used to solve the equations, such as the perturbation method. Assumptions are used to analyze the flow. The effect of Hartmann number (Ha), Darcy number (Da), material fluid (We), magnetic field (β), capacitance ratio (∅) and rotation are calculated(Ω)Numerical results were calculated using MATHEMATICA program